PENGEMBANGAN INSTRUMEN NUMERASI PADA KONTEKS PERTANIAN DAN PARIWISATA UNTUK SISWA KELAS 4 SEKOLAH DASAR - Najwa, Wulida Arina; Najwa, Nibras Alhama (Jurnal keilmuan dan Kependidikan dasar, 2023)
The Minimum Competency Assessment (AKM) is one of the newest forms of assessment issued by the Ministry of Education and Culture. AKM is designed to measure student achievement from cognitive learning outcomes, namely reading literacy and numeracy. Numerical ability is related to the application of basic knowledge and mathematical principles and processes in everyday life. Agriculture is one of the fields that apply the basis, concepts, principles and processes of mathematics in its use. Then tourism which is part of local wisdom can develop knowledge, problem solving and student character. This study aims to develop numeracy questions that are used to measure cognitive aspects in the form of numeracy abilities of elementary school (SD) students through AKM. The method used in this study is the Research and Development (R&D) method. The steps in developing the assessment instrument are (1) compiling test specifications, (2) writing questions, (3) examining the contents of the questions, (4) improving the contents of the questions, (5) conducting trials, (6) analyzing each item, (7 ) interpret the test results. The data analysis used is the Gregory formula to test its validity, and the Guilford formula to test its reliability. Based on the Gregory formula, the results obtained in this study were 0.8 with very high validity criteria. As for reliability using the Guilford formula, the results obtained are 0.717 with high reliability criteria.